STUDY OF SHORELINE CHANGES AT JENEBERANG RIVER DELTA, MAKASSAR - Sakka Sakka; Mulia Purba; I Wayan Nurjaya; Hidayat Pawitan; Vincentius P. Siregar (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2011)
The study of shoreline changes during 1990 - 2008 in the delta of the River Jeneberang, Makassar was conducted by evaluating sediment transport into and out of a cell. Longshore sediment transport was computed by considering the influence of heights and angles of the breaking waves. Results of calculation of sediment transport showed that the dominant of sediment transport was to the north during the arrival of the southwest and west waves, and to the south when the wave coming from the northwest. Comparison between shore profiles resulting from model and coastline satellite imagery showed similarity. The difference between the two tend to be occurred at the head land part of the shoreline. This was due to complexity of coastal dynamic at the area. The results of the 19 years shoreline simulation showed that there was a tendency of abrasion at the upsteam head land part as the wave energy tend to converge and accretion at the bay part as the wave energy tend to diverge. Abrasion mainly occurred at Tanjung Bunga (head land) where the coast retreat 181.1 m. Accretion occur in the bay area (Tanjung Merdeka) where the coast advance to the sea for about 59.8 m. The shoreline tend to be stable when the profile was straight such as Barombong Coast.Keywords: abrasion, accretion, sediment transport, shoreline changes.